1999
DOI: 10.1002/(sici)1098-2779(1999)5:4<314::aid-mrdd9>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Proopiomelanocortin (POMC) disregulation and response to opiate blockers

Abstract: Autism is a collection of disorders or subtypes with distinctive or prominent phenotypes and genotypes. The study of adults with autism offers a unique opportunity to examine its phenotypic diversity. Recent evidence has identified disturbances in specific neurochemical systems that are associated with primary autistic symptoms. Establishing biological markers, such as specific neurochemical disturbances, not only confers greater precision in phenotyping individuals but also provides the basis for rational int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 85 publications
1
37
0
1
Order By: Relevance
“…Indeed, numerous studies from many laboratories have shown that the functioning, relations, and processing of the POMC system are uncoupled or perturbed in subgroups of self-injuring individuals, resulting in different ratios of βE and ACTH, particularly under conditions of stress (Leboyer et al, 1994(Leboyer et al, , 1999Gillberg, 1995;Cazzullo et al, 1999;Sandman et al, 1990aSandman et al, , 1990bSandman et al, , 1995Sandman et al, , 1997Sandman et al, , 1999Sandman et al, , 2000aSandman et al, , 2002Sandman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies from many laboratories have shown that the functioning, relations, and processing of the POMC system are uncoupled or perturbed in subgroups of self-injuring individuals, resulting in different ratios of βE and ACTH, particularly under conditions of stress (Leboyer et al, 1994(Leboyer et al, , 1999Gillberg, 1995;Cazzullo et al, 1999;Sandman et al, 1990aSandman et al, , 1990bSandman et al, , 1995Sandman et al, , 1997Sandman et al, , 1999Sandman et al, , 2000aSandman et al, , 2002Sandman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism relating SIB to opioids is the finding of a dysregulated POMC or opioid system in an estimated 30-70 % of individuals with SIB (Sandman et al 1999). The precursor POMC is considered to be a stressrelated molecule and its products, BE and ACTH, are part of the hypothalamic-pituitary-adrenal axis.…”
Section: Opioid Systemmentioning
confidence: 99%
“…Behavioral intervention techniques, which can be used for assessing [Iwata et al, 1982] and intervening with most forms of SIB, burgeoned in the 1980s. In the 1990s the interaction of these trends to study gene-environment interactions [Sackett, 1999], environmental effects on neurotransmitter functions [Tessel et al, 1995], and their combination [Thompson et al, 1995;Sandman et al, 1999] have predominated. The next decade holds new promise for developing a more comprehensive and theoretically driven approach to the study of this devastating disorder, its intervention, and ultimately its prevention.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that a comprehensive examination of the POMC molecule and the genes that control its expression may be a productive strategy to better understand a biological pathway relevant to SIB. Sandman et al [1999] have initiated such studies and have preliminary evidence of a mutation in the opioid region of the POMC gene.…”
Section: Opioids Addiction and Stress In The Maintenance Of Sibmentioning
confidence: 99%